A phylogeny and classification of the Talitroidea (Amphipoda, Senticaudata) based on interpretation of morphological synapomorphies and homoplasies - Myers, A.a.; Lowry, J.k. (Zootaxa, 2020)
A morphological cladistic analysis was carried out on talitroid Amphipoda. Each character state was carefully analysed to determine whether it could be most parsimoniously ascribed to a synapomorphy or to a homoplasy. Within the Talitroidea, two new epifamilies, the Protorchestoidae and the Talitroidae, six new families, the Uhlorchestiidae, the Protorchestiidae, the Arcitalitridae, the Brevitalitridae, the Curiotalitridae and the Makawidae and three new subfamilies in the Talitridae, the Talitrinae the Floresorchestiinae and the Pseudorchestoidinae are established. A formal classification is provided to the level of subfamilies. Families and subfamilies are diagnosed.